Clinical Assessment and Rehabilitation Treatment of Shoulder-Hand Syndrome after Stroke - Zhang, Jing (Journal of Contemporary Medical Practice, 2025)
Shoulder-Hand Syndrome (SHS), as a common complication of stroke, significantly impacts the rehabilitation efficacy and recovery progress of stroke patients. In clinical practice, there are numerous evaluation methods and treatment approaches for this condition. This article discusses the commonly used assessment techniques and their roles, as well as treatment methods in current clinical practice, aiming to provide insights for targeted evaluation and rehabilitation therapy of this syndrome.